RISK-BASED AUDIT ATAS PENJUALAN PADA PT âXâ - Lusy, Lusy (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
Selling is the element which has an important role for a company, since the company earns income which will be used as source of funding from this activity, for the companyâs sustainability. By holding an audit of sales, it is expected that audit can fulfill the needs of information which is free from deviations, in order to make the implementation of audit can be performed efficient and effectively and the achievement of companyâs objectives. This research is meant to develop Risk-based Audit method on sales at PT âXâ. By using Risk-based Audit, the risks which exist on the company can be predicted and their occurrence can be reduced before it comes to reality, and the potential risk, its source and recommendation which will occur can be analyzed. Qualitative research method and case study approach is used in this research. The result of the research shows that the source of risk lies in the lack of procedures and systems (either in terms of process, human resources, or internal control), and some company policies which are not strict in running companyâs operational.Keywords: Internal Audit, Risk-based Audit, and Test of Control